Autonomy in the AAL : between law and ethics - Bieskova, Mariia (My University, 2019)
The growth of Silver Economy calls for a paradigm shift in senior care, where active and healthy ageing is a primary goal. It also coincides with the rapid development of new technologies – AAL being one of them. The AAL combines the advances in the emerging technologies with the need to promote healthy and active ageing experience. This master thesis focuses on the value of individual autonomy and its importance in the context of senior care. The main argument of this research is that individual autonomy is a crucial element in attaining the goal of active and healthy ageing. However, the impact of AAL technology on individual autonomy is uncertain. On one side, AAL's main goal is to enable independent and autonomous living for as long as possible, while on the other side, the AAL by its very design limits individual autonomy. Individual autonomy in the AAL is enabled through legal and ethical norms. The nature of the AAL technology and the contexts and norms under which it operates are dynamic and constantly changing. Therefore, legal regulation needs to be augmented by ethical norms that are fit to meet the ever-changing character of this emerging technology. In particular, ethical technology design principles have a great potential to address the novelty of the AAL and the challenges that European data protection legislation is failing to tackle.
Keywords: AAL, Ambient Assisted Living, eHealth, mHealth, Privacy, Autonomy, Social Care, Senior Care, Data Protection, Right to Private Life, Ethics, Ethical Design, General Data Protection Regulation, GDPR, Bioethics, Medical Ethics, Ethics of Technology, Contextual Integrity, Senior, Older Person